(untitled) (Research, Society and Development, 2020)
Objective. Report the trajectory of a life marked by prejudice and social exclusion due to the stigma of Psoriasis, with special emphasis on the case report and experience that has helped me with my autoimmune disease. I have psoriasis, a disease that manifests itself by lesions on the skin, in the form of red and whitish plaques. Psoriasis has no cure, although the cause is not known, as in many autoimmune diseases, psoriasis is not a contagious disease, psoriasis is not caught by contact. It also does not cause any type of pain or more serious discomfort for the patient, at least with regard to the physical part (I am referring to psoriasis vulgaris, which is my type). The injuries usually frighten people a lot, which end up avoiding contact with the patient and creating isolation, which usually worsens over the years and the disease gets worse. Method. The information was obtained through a case report, of a descriptive type, of a subjective character, obtained during the period from 2015 to 2020. Discussion. The present report was based on research of scientific articles, which deal with subjects pertinent to psoriasis (stigma, social exclusion, Social Interaction). Final considerations. Difficulties in interacting socially are not exclusive to people with skin disease, but such individuals are especially vulnerable to them, since the skin is the body organ most exposed and extremely important for the construction of personal identity and subjectivity.